[Review] Mobilities, Networks, Geographies - Korstanje, Maximiliano E (2017)
This book reviews exerts a radical critique on the recently updated version of Mobilities, Networks, Geographies, though the theory of mobilities offer an interesting explanation of how capitalism connects peopls, cultures and markets, no less true is that it lacks of an historical exploration of the history of nationstate, which would helps expanding the understanding of mobitliies as a simple discourse, oriented to discipline citizens.Larsen, J.; Urry, J. & Axhaussen, K. (2016). Mobilities, Networks, Geographies. Abingdon: Routledge. ISBN 978-075464882-6